2022
DOI: 10.3390/businesses2020012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Youth’s Willingness to Exploit Agribusiness Opportunities in Nigeria with Entrepreneurship as a Moderating Variable

Abstract: Despite various initiatives and investments in youth entrepreneurship and start-ups, youth participation in agribusiness has not significantly increased. Therefore, this study analyzed the perceived effects of entrepreneurial traits on youth’s willingness to exploit agribusiness opportunities in Nigeria. A total of 3600 respondents were randomly selected across Nigeria using an online well-structured questionnaire. The data were analyzed using a binomial logistic regression among other tools. The study found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, the National Bureau of Statistics (NBS) (2020), found that unemployment rate in Nigeria is on a steady increase. Therefore, Agroenterprises must be established in agriculture-based developing countries, like Nigeria to stimulate economic growth and provide employment and income generation for aspiring entrepreneurs (Ikuemonisan, Mafimisebi, Ajibefun, Akinbola, & Oladoyin, 2022). According to various studies, however, Nigerian government is re-diversify towards agriculture in order to improve GDP and reduce unemployment (Uzonwanne, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the National Bureau of Statistics (NBS) (2020), found that unemployment rate in Nigeria is on a steady increase. Therefore, Agroenterprises must be established in agriculture-based developing countries, like Nigeria to stimulate economic growth and provide employment and income generation for aspiring entrepreneurs (Ikuemonisan, Mafimisebi, Ajibefun, Akinbola, & Oladoyin, 2022). According to various studies, however, Nigerian government is re-diversify towards agriculture in order to improve GDP and reduce unemployment (Uzonwanne, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The making of more beneficial and useful youth service and engagement in the livestock subdivision is the fundamental road-map to diminishing neediness. For this, one significant objective will be to further develop the market placement and commercialization of livestock production activities, likewise with a view to economical heightening and coming about expansions in efficiency (Chams & García-Blandón, 2019;Edamisan Stephen Ikuemonisan et al, 2022). Unswerving information on workforce markets is scant, likewise the deficiency of information on youth input as well as their view of business in animal production as a profession.…”
Section: Introductionmentioning
confidence: 99%